Repeat Offenders: Violence and Textual Economy - Scott Shinabargar (Studies in 20th & 21st Century Literature, 2005)
L'acte surréalistite le plus simple consiste, revolvers aux poings, à descendre dans la rue et à tirer au hasard, tant qu'on peut, dans la foule. (Breton, Manifestes 155) It is difficult not to feel uncomfortable reading this well-known passage now, in light of recent events. And yet, isn't this perhaps precisely the reason such a text demands our attention? By studying similar passages in Breton's writing, we find that it is through a very particular use of language that the alienated subject acquires a sense of empowerment; and more importantly, that the force of such a discourse is extremely limited—dependent on a destructive relation to alterity—precisely where it promises liberation. Through close textual analysis, we observe that the "terrorist" writer in fact ends up reproducing, and indeed exacerbating the very process of devaluation he has set out to transcend. As the writer increasingly fixates on oppressive institutions and conventions, the insistence of his invective—a repetition compulsion we find establishing itself in the very prosodic structures of the text—generates a language which, instead of opening out onto new possibilities for meaning, produces semantic homogeneity.
Keywords: Breton; Manifestes; alienated subject; empowerment; alterity; discourse; textual analysis; terrorist; oppressive institutions; institutions; conventions; prosodic structures; structures; semantic homogeneity